2016
DOI: 10.1177/2156587216676122
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and Cancer-Related Fatigue and the Interrelationships With Depression, Stress, and Inflammation

Abstract: Cancer-related fatigue (CRF) is a common symptom experienced in cancer patients. Depression, anxiety, and stress are associated with cancer. Depression and anxiety are also associated with CRF. At the cellular level, much is known about the impact of stress on the body generally, and its potential role in cancer. Stress, anxiety, and depression have been found to depress the immune system. Depression and stress have also been found to create inflammatory changes in the body and there is emerging evidence that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 65 publications
(89 reference statements)
4
46
0
3
Order By: Relevance
“…This finding suggests that some psychological symptoms may form a fairly stable symptom cluster with CRF. It also supports the possibility that anxiety and depression add to the stress response and weaken the immune system, triggering inflammatory mediators involved in CRF and leading to pro‐inflammatory changes in the body . These findings are aligned with reviews reporting depression and anxiety as prominent correlates of CRF, and lend strength to the argument that psychological distress needs to be accounted for when investigating the usefulness of leptin as a biomarker for CRF.…”
Section: Discussionsupporting
confidence: 73%
“…This finding suggests that some psychological symptoms may form a fairly stable symptom cluster with CRF. It also supports the possibility that anxiety and depression add to the stress response and weaken the immune system, triggering inflammatory mediators involved in CRF and leading to pro‐inflammatory changes in the body . These findings are aligned with reviews reporting depression and anxiety as prominent correlates of CRF, and lend strength to the argument that psychological distress needs to be accounted for when investigating the usefulness of leptin as a biomarker for CRF.…”
Section: Discussionsupporting
confidence: 73%
“…A cancer diagnosis and its treatments are stressful experiences for most patients. 1,2 The coronavirus disease 2019 (COVID-19) pandemic and associated mitigation procedures have imposed additional stress. Emerging evidence suggests that fear of infection, concerns regarding the efficacy of COVID-19 treatments, the negative impact of various mitigation procedures (e.g., social isolation), and economic uncertainty are associated with higher levels of perceived stress in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic arm lymphedema after breast surgery impairs physical performance and studies have shown that early mobilization and rehabilitation have improved outcomes [23]. It is imperative that the patient's physical symptoms be addressed early and adequately as physical disability often leads to depression [24].…”
Section: Discussionmentioning
confidence: 99%